Strategi Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana dalam Mencegah Kekerasan Perempuan di Kota Batam - Nelly; Lubna Salsabila (SCIENTIA JOURNAL, 2022)
Law Number 7 of 1984 concerning the Ratification of the Convention on the Elimination of All Forms of Discrimination and Violence against Women. The purpose of this research is to describe in the Strategy of the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Preventing Violence against Women in Batam City and to analyze the inhibiting factors in the Strategy of the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Preventing Violence against Women in Batam City the type of research method used is descriptive research method with a qualitative approach using interview, observation, and documentation data collection techniques. The data sources of this researcher consist of primary data and secondary data. The results showed that the Strategy of the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Preventing Women's Violence in Batam City was good but needed to improve the performance required by victims of violence against women. Based on the conclusions and results of the study, researchers used indicators from LAN-RI which were based on five indicators used as follows: Input Indicator (Input), Output Indicator (Output), Outcome Indicator (Results), Benefit Indicator (Benefit) and Impact Indicator (Impact) namely improving existing facilities and infrastructure at the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Preventing Violence against Women in Batam City, Violence against women is increasing with news and news reports, counseling and socialization in preventing violence against women in Batam. Batam City, received facilities in the form of spiritual support, mentoring, felt protected, and demanded their rights, and the positive impact of preventing violence against women made victims feel safe with the facilities provided by the service from psychologists and assistance.